Identifikasi Strategi Pengembangan Pariwisata Berbasis Ekonomi Kreatif Sebagai Bentuk Perluasan Kesempatan Kerja di Desa Wisata Bilebante - Nurholid Satriawan; Lalu Hendra Wirawan; Rena Tilla Qur’Aini; Arum Wulansari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Tourism is one of the sectors that is growing rapidly in Indonesia and is a major contributor to the country's foreign exchange. Tourism development through tourist villages, such as the Bilebante Green Tourism Village in West Nusa Tenggara, is an effective strategy for improving the local economy and preserving cultural traditions. This research aims to identify and analyze creative economy-based tourism development strategies in the Bilebante Green Tourism Village. The theory used is rational choice which was coined by James S Coleman. The research method used is a qualitative method with a phenomenological design. The data collection technique is carried out in several processes, namely observation, in-depth interviews, and documentation in order to obtain valid data. The data analysis technique uses the Miles and Huberman interactive model. Informants consisted of community leaders, village managers, culinary traders and tour guides. The results of this research focus on 2 aspects, namely tourism development and creative economic factors as drivers of employment opportunities. The green tourism village of Bilebante is able to develop because actors (tourism managers) are able to map resources well so that this has implications for the right development choices. Local people in this case are also able to choose jobs freely based on the skills resources they have.